DIGITALISASI PEMASARAN KUE BASAH DALAM MENGHADAPI PERSAINGAN DAGANG SELAMA PANDEMI COVID-19 - Dewi Asiyah; Adelia Handoko (Dinamika Journal : Pengabdian Masyarakat, 2021)
The emergence of Covid-19, which has spread to almost all countries in the world, has had a significant impact in various sectors, one of which is the existence of Micro, Small and Medium Enterprises (UMKM). This pandemic has caused many workers to decrease or even lose their income, thus affecting the level of consumption and purchasing power of the people. This causes a decline in people's purchasing power for consumer goods and puts pressure on producers and sellers. This impact is clearly felt by the business actors of wet cakes in Banjarejo Village, Rejotangan District, Tulungagung Regency, East Java. The existence of the Back to Village Real Work Lecture program (KKN BTV) at the University of Jember aims to assist entrepreneurs in the cake business in Banjarejo Village. More specifically, the purpose of this activity is to provide education, training and assistance on branding and digital marketing. The method used in this KKN BTV activity is planning, implementation and evaluation. The efforts that have been made to realize branding and digital marketing have been realized with the creation of logos and packaging labels as well as the formation of an Instagram account as a digital marketing medium. The existence of education, training and mentoring resulted in an increase in target knowledge of branding by 25% and knowledge about digital marketing by 30%. Respondents are more interested in cakes that have logos and packaging labels that are more informative. 100% of respondents said product photos after editing are more interesting and good than before editing. It is also easier for consumers to see references and information on wet cakes produced by the target through Instagram.